Caribbean Report 10-03-1993 - Ransome, Debbie (anchor); Meeks, Brian (interviewee); Williams, Eddie (correspondent); Islam, Shada (correspondent); Rapier, William (interviewee) (The British Broadcasting Corporation, 1993)
Jamaican Prime Minister PJ Patterson announces the general election date to the Jamaican people, the date coincides with the date he gained victory over the then Michael Manley administration – correspondent Debbie Ransome reports from an interview with Jamaican Political Scientist Dr. Brian Meeks, who gives his political analysis of Prime Minister’s Patterson’s chances of a victory. The Netherlands Antilles as an overseas dependency of Holland appears likely to be dismantled. However the process towards granting internal self government to the islands which make up the group seems headed to controversy. Officials are meeting in Curacao to work out a new format for administering the islands – correspondent Edie Williams reports. Life on the Dutch side of St. Maarten was returning to normal as the protest organized by the United St. Maarten Organization, in St. Maarten-Phillipsburg in protest for the dissolution of the current Dutch St. Maarten government has been called off. British Fruit Distribution Company – Geist, says that a misunderstanding led to a confidential report to Windward island leaders accusing the company of overcharging for shipping arrangements- saying that the company wanted servicing charges not full payment for its ships. William Rapier - Chairman of Geist Industries West Indies Ltd. Provides clarity on the situation in an interviewee with correspondent Debbie Ransome.In Strasburg, Germany - a German Euro Socialist MP organized an unusual banana tasting ceremony in an attempt to diffuse the tensions over the European Banana market. He wanted to prove that when it came to taste, Caribbean and Central American bananas were not very different and consumers in Europe should have a wider choice and plans to promote this by organizing future banana tasting ceremonies in different parts of Germany - correspondent Shada Islam reports.
Headlines with anchor Debbie Ransome (00:00-00:34).
1. Jamaican Prime Minister PJ Patterson announces the general election date to the Jamaican people (00:35-05:25).
2. The Netherlands Antilles as an overseas dependency of Holland appears likely to be dismantled (05:26 -07:28).
3. Life on the Dutch side of St. Maarten was returning to normal as the protest organized by the United St. Maarten Organization, in St. Maarten-Phillipsburg in protest for the dissolution of the current Dutch St. Maarten government has been called off (07:29 – 08:00).
Keywords: Jamaica--Politics and government.; Elections—Jamaica.; Netherlands Antilles--Politics and government.; Caribbean Area--Politics and government.; Caribbean Area--Commerce.; Caribbean Area--Commerce.; Europe--Commerce--Latin America.; Europe –Commerce--Caribbean Area.; Bananas—Commerce--Europe.; Bananas—Commerce—Latin America.